Southern Mediterranean development through trade, Foreign Direct Investment and migration - Hong, Wai Mun; Lorca, Alejandro V.; Medina Moral, Eva (Papeles de Europa, 2010)
Since the launch of the Barcelona Process in 1995 and later the Euro-Mediterranean Partnership, economic relationship between the European Union (EU) and Southern Mediterranean has grown tremendously. Trade volume, in terms of absolute value, between the EU and Southern Mediterranean has grown to an unprecedented height. Although the value has increased, foreign direct investment (FDI) from the EU to Southern Mediterranean remains low. South-to-North migration has also undoubtedly increased given the fact that it has become one of the priority concerns of the EU. Development has taken place through these economic exchanges. However, economic development growth rate remains considerably low compared to that of Latin America and Southeast Asia. This paper discusses about the economic development dynamic of Southern Mediterranean in comparison with that of Latin America and Southeast Asia through economic indicators, economic openness and trade, FDI and migration flows and structures. It also discusses about the challenges faced by Southern Mediterranean and how the economic crisis in the EU may affect their economic relationship.